The books of problems in arithmetic by Mikas Petrauskas - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2013)
Teacher Mikas Petrauskas (1908?) was the last author having published his books of problems in arithmetic for I-III forms of primary school in Independent Lithuania before the World War Two. As books of problems by other authors of the said period, the books of problems by M. Petrauskas distinguished themselves for expressed integration of arithmetic teaching with the real life of the pupils. The books of problems were used in Lithuania during the World War Two and at schools for children of war refugees in the post-war period at West Germany. M. Petrauskas was the only author that dared to publish reviewed books of problems in post-war Soviet Lithuania. However, the said review was not natural and integration with the real life was engaged considerably in the political aspect. The attempts were ineffective: within 5 years, books of problems by M. Petrauskas were displaced from Lithuanian schools by the ones approved in Moscow and translated from Russian.
Keywords: books of problems in arithmetic; primary school; independent Lithuania before the world war two and Soviet Lithuania; war refugees from Lithuania in the post-war period; West Germany